Modeling aggregate behavior and fluctuations in economics : stochastic views of interacting agents - Aoki, Masanao (Cambridge University Press, 2002)
How do a large but finite number of agents interact, and, consequently, what macroeconomic statistical regularities or patterns may evolve? The book examines situations (e.g. fluctuations about equilibria, multiple equilibria and asymmetrical cycles of models) which are caused by model states stochastically moving from one basis of attraction to another.